2008
DOI: 10.5664/jcsm.27074
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Regular Exercise, Depression, and Degree of Apnea are Predictors of Excessive Daytime Sleepiness in Patients with Sleep Apnea: Sex Differences

Abstract: E xcessive daytime sleepiness (EDS) is very common in modern societies. In the general population, the prevalence of EDS is estimated to range between 5% and 20%. [1][2][3][4][5][6][7][8][9] EDS and fatigue are the most common complaints of patients referred to the sleep disorders clinic. 10,11 Moreover, they are potential risk factors for cardiovascular disease and mortality, 12,13 are associated with a negative perception of general health and quality of life, 14,15 and raise major public safety concerns. 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(55 citation statements)
references
References 53 publications
2
50
0
3
Order By: Relevance
“…First, EDS is closely associated with traditional cardiovascular risk factors, such as obesity, diabetes mellitus, uncontrolled hypertension, and physical inactivity. [22][23][24][25] It is conceivable that mechanisms implicated in CVD risk (eg, inflammation 26 ) may also underlie EDS. Second, aside from SDB, insufficient sleep and other sleep disorders such as insomnia, which may undermine patients' sleep quality and cause EDS, have also been associated with poor cardiovascular outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, EDS is closely associated with traditional cardiovascular risk factors, such as obesity, diabetes mellitus, uncontrolled hypertension, and physical inactivity. [22][23][24][25] It is conceivable that mechanisms implicated in CVD risk (eg, inflammation 26 ) may also underlie EDS. Second, aside from SDB, insufficient sleep and other sleep disorders such as insomnia, which may undermine patients' sleep quality and cause EDS, have also been associated with poor cardiovascular outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Because EDS is a frequent symptom of several CVD conditions, 12,33 chronic disease management rather than stimulant therapy may reasonably be prioritized to alleviate EDS and to improve cardiac outcomes as well. Meanwhile, because several preventable risk factors for coronary artery disease, such as inactivity, obesity, and a high-carbohydrate diet, 22,24,34 are closely related to EDS, lifestyle adjustment may be recommended. As one of the most important symptoms of moderate to severe SDB, the presence of EDS is an indicator for CPAP therapy.…”
Section: Discussionmentioning
confidence: 99%
“…A correlation between depression and daytime sleepiness has been reported in the general population 7 as well as in patients with OSA. 17,[25][26][27] Ishman et al 26 showed that ESS was significantly associated with depressive symptoms measured by BDI Fast Screen after controlling for race, sex, age and RDI. Kjelsberg et al 27 showed that ESS and low compliance with continuous positive airway pressure therapy were the only predictors of high level of depression measured by the Hospital Anxiety and Depression scale.…”
Section: Comparisons With Other Studiesmentioning
confidence: 99%
“…Examination of patients with anxiety and depression showed that their sleep patterns were irregular [14]. While it was reported that the incidence of depression in the adult population was between 3% and 10% [15], certain studies demonstrated that the depression incidence was between 20-40% in patients with OSAS [4,16,17]. OSAS may cause depression via sleep loss, sleep disruption, and cognitive changes induced by intermittent hypoxemia, while weight gain and sleep disruption due to depression could cause OSAS [8].…”
Section: Introductionmentioning
confidence: 99%